2010
DOI: 10.1080/03079451003599284
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and parasitological tools for the study ofAscaridia gallipopulation dynamics in chickens

Abstract: Experiments were first conducted to compare and evaluate different methods of Ascaridia galli larval recovery from the chicken intestine. The number of larvae recovered from the intestinal wall of chickens infected with 1000 embryonated A. galli eggs and killed 15 days post infection (p.i.) by three methods (ethylenediamine tetraacetic acid [EDTA], pepsin digestion and scraping) were compared. The EDTA and pepsin digestion were found to be the most efficient methods with no significant difference (P!0.05) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…However, species identification was based on molecular analysis, which was performed by establishing consensus with partial sequences of the 18S small subunit ribosomal RNA (rRNA) gene and mitochondrial gene COI. The identification based on 18S rRNA showed that the specimen shared 99% of its maximum identity with A. galli when compared with specimen number EF180058 deposited in GenBank (NADLER et al, 2007); it also shared 100% of the maximum identity with the COI gene when compared with the haplotype obtained from chickens from an organic farm in Europe (KATAKAM et al, 2010). The sequences of A. galli in the present study were submitted to GenBank under the previously established accession numbers KP982856 and KP982857 for the COI gene sequence and 18S rRNA sequence, respectively.…”
Section: Ancylostomatidaementioning
confidence: 99%
“…However, species identification was based on molecular analysis, which was performed by establishing consensus with partial sequences of the 18S small subunit ribosomal RNA (rRNA) gene and mitochondrial gene COI. The identification based on 18S rRNA showed that the specimen shared 99% of its maximum identity with A. galli when compared with specimen number EF180058 deposited in GenBank (NADLER et al, 2007); it also shared 100% of the maximum identity with the COI gene when compared with the haplotype obtained from chickens from an organic farm in Europe (KATAKAM et al, 2010). The sequences of A. galli in the present study were submitted to GenBank under the previously established accession numbers KP982856 and KP982857 for the COI gene sequence and 18S rRNA sequence, respectively.…”
Section: Ancylostomatidaementioning
confidence: 99%
“…Nematodes of the genus Ascaridia are known to infect many species of birds causing fatal diseases. The small intestine is a principal target organ of A. galli infection ( Katakam et al, 2010 , Luna-Olivares et al, 2012 , Taylor et al, 2007 ). Previous study ( Fatihu et al, 1990 , Luna-Olivares et al, 2012 ) showed that most of the helminth parasites were restricted to the small intestine, particularly the duodenum where there are optimum concentrations of saline and glucose.…”
Section: Discussionmentioning
confidence: 99%
“…A. galli is the most common nematode in poultry [6,11], having a direct life cycle in the intestinal tract with a larval migratory phase into the enteric wall [13]. Penetration of the parasite into the small intestine mucosa may cause hemorrhagic to necrotic enteritis, associated with anemia and diarrhea [14].…”
Section: Discussionmentioning
confidence: 99%